Two faces of Solanaceae telomeres: a comparison between Nicotiana and Cestrum telomeres and telomere-binding proteins - Peska, V; Sýkorová, E; Fajkus, J (Cytogenetic and genome research, 2008)
While most Solanaceae genera (e.g.Solanum, Nicotiana) possess Arabidopsis-type telomeres of (TTTAGGG)n maintained by telomerase, the genera Cestrum, Vestia and Sessea (Cestrum group) lack these telomeres. Here we show that in the Cestrum-group the activity of telomerase has been lost. Nevertheless, proteins binding the single-stranded G-rich strand of the Arabidopsis-type and related human-type (TTAGGG)n telomeric sequences are present in nuclear extracts of both Nicotiana and Cestrum species. These proteins may have a role in telomere function or other cellular activities. In addition to characterizing DNA binding specificity and molecular weights of these proteins, we searched in both N. tabacum (tobacco) and C. parqui for the presence of POT1-like proteins, involved in telomere capping and telomerase regulation. Analysis of POT1-like proteins available on public databases and cloned by us from C. parqui, revealed the N-terminal OB folds typical for this protein family and a novel, plant-specific conserved C-terminal OB-fold domain (CTOB). We propose that CTOB is involved in protein-protein interactions.
Keywords: Electrophoresis, Polyacrylamide Gel; sekvenční seřazení; Nicotiana; Telomere-Binding Proteins; telomerasa; sekvenční homologie aminokyselin; elektroforéza v polyakrylamidovém gelu; Sequence Homology, Amino Acid; telomery; Molecular Sequence Data; Electrophoretic Mobility Shift Assay; molekulární sekvence - údaje; Telomerase; konzervovaná sekvence; amplifikace genu; Solanaceae; retardační test; Amino Acid Sequence; Conserved Sequence; proteiny vázající telomery; Telomere; Gene Amplification; rostlinné proteiny; Cestrum; tabák; Sequence Alignment; Plant Proteins; sekvence aminokyselin